2016
DOI: 10.16997/jdd.245
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Deliberative Pedagogy: Using a Learning Outcomes Rubric to Assess Tradeoffs and Tensions

Abstract: Teaching deliberative decision-making is a method of encouraging students to think critically, engage public problems, and engage in both public speaking and public listening. College instructors have begun to use deliberation as a pedagogical tool, yet further research is needed to understand the learning outcomes of deliberative pedagogy. We argue that the deliberative principle of "understanding tradeoffs and tensions" is a key learning outcome of deliberative pedagogy, and demonstrate an avenue for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The rhetorical analysis of deliberation frequently 'focus [es] on the connections among communication, democracy, knowledge and power', and offers insights to how argument impacts 'prudence, practical wisdom and judgment' (Carcasson, Black & Sink 2010: 4-5). Using this methodology, scholars have studied the argumentation of public deliberation in a variety of formal and informal communication settings, including policy and legislative debates, school boards, community public forums, classrooms and online message boards (Adams 2014;Asen 2015;Asen et al 2011;Bates & Lawrence 2014;Drury et al 2016;Levasseur & Carlin 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhetorical analysis of deliberation frequently 'focus [es] on the connections among communication, democracy, knowledge and power', and offers insights to how argument impacts 'prudence, practical wisdom and judgment' (Carcasson, Black & Sink 2010: 4-5). Using this methodology, scholars have studied the argumentation of public deliberation in a variety of formal and informal communication settings, including policy and legislative debates, school boards, community public forums, classrooms and online message boards (Adams 2014;Asen 2015;Asen et al 2011;Bates & Lawrence 2014;Drury et al 2016;Levasseur & Carlin 2001).…”
Section: Methodsmentioning
confidence: 99%
“…They advocate a rehabilitation of expertise to orient more towards localized norms and understanding. Yet Levasseur and Carlin's (2001) research on public deliberation found that citizens are likely to rely on egocentric argumentation when discussing public issues, although Drury et al (2016) note that training in public deliberation may mitigate this tendency and Escobar (2014: 171-176) shows how facilitators can enable participants to shift from private to public reasoning. Furthermore, when deliberations are designed with opportunities for engagement and questioning of technical expertise, participants then incorporate evidence from the technical sphere into a more public reasoning, bringing expertise alongside local engagement and knowledge (Gastil & Knobloch 2020;Roberts et al 2020;Sprain, Carcasson & Merolla 2014).…”
Section: Socioscientific Wicked Problems Argumentation and Deliberative Qualitymentioning
confidence: 99%
“…In weighing trade-offs and tensions, participants explore a range of possible options, evaluation, and ultimately, synthesize a preferred solution. The idea that "even the 'best' solution has tradeoffs" is a somewhat "new way of thinking," one rarely expressed in political discourse (Drury et al, 2016). Weighing trade-offs and tensions moves a deliberating group past the potential paralysis of "agree to disagree," as participants acknowledge potential trade-offs as needing to be accepted, managed, or transcended if they move forward with a preferred action.…”
Section: Practical Wisdom Weighs Trade-offs and Tensionsmentioning
confidence: 99%
“…Research on deliberative pedagogy tends to be directed at the interaction process of learning in the classroom and school, even though the problems discussed have begun to originate from real events in the community (Goodin & Stein, 2008;Ibrahim, 2015;Samuelsson, 2016;Drury, Andre, Goddard & Wentzel, 2016). Deliberative learning in class is considered insufficient to form the capabilities of citizenship.…”
Section: Introductionmentioning
confidence: 99%